Analisis Media Monitoring terhadap BPJS Kesehatan di Tengah Lonjakan Kasus DBD di Indonesia pada Februari-Maret 2024 - Marva Razita Ramelan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
In early 2024, deaths from Dengue Hemorrhagic Fever (DHF) increased again in Indonesia, with the number of cases higher than the previous year. This condition raises concerns because DHF remains a serious public health problem. The World Health Organization (WHO) emphasized that the key to reducing mortality lies not only in early detection but also in public access to fast, effective, and equitable health services. This statement aligns with the second point in the document